The Relationship Between Macroeconomy and Asset Prices: Long Run Causality Evidence From Lithuania - Jurkšas, Linas; Paškevičius, Arvydas (Organizations and Markets in Emerging Economies, 2017)
The purpose of this paper is to determine the long-run causal impact of various economic factors on Lithuanian stock, government securities and real estate prices, and to assess how accurately future asset returns can be forecasted based solely on economic information. Five macroeconomic indicators, namely, gross domestic product (GDP), foreign direct investment (FDI), consumer price index (CPI), money supply (MS) and Vilnius interbank offered rate (VILIBOR), were included in the model. The results of the created autoregressive distributed lag model (ARDL) revealed that a long-run causal relationship between Lithuanian assets and macroeconomic variables exists and that changing values of these indicators explain about half of the variability of assets’ returns. The results of ARDL model forecast showed that the most precise predictions are obtainable in real estate market, while forecasted returns of stock and government securities are not so accurate, especially the further forecast horizon. The possibility to understand driving factors behind changes of asset prices and to predict future return is of a particular importance not only for investors and businessmen, but also for the policy makers who are responsible for making substantiated decisions regarding monetary, macroprudential and fiscal policies they conduct.